23. Dnevi varstvoslovja, Laško, 8. in 9. junij 2022 : Zbornik povzetkov (University of Maribor Press, 2022)
23rd Conference Days of Criminal Justice and Security . Contributions of the 23rd Conference Days of Criminal Justice and Security represent professional and scientific consideration of paths and resources for provision of security in contemporary society. The book of abstracts includes abstracts of two plenary lectures, two round tables and forty-four contributions, dealing with a broad range of topics such as policing, private security, security and safety in local communities, criminal investigation, criminology, complaint procedures, private detective activities, the implementation of criminal sanctions, cyber security, technologies in the security provision, and other current security challenges of contemporary society.